A novel integrated suspension tilting system for narrow urban vehicles. (December 2018) - Tang, Chen; Goodarzi, Avesta; Khajepour, Amir
Narrow vehicles are proposed to resolve urban transportation issues such as congestion, parking, fuel consumption and pollution. They are characterized by a high ratio of centre of gravity height over track width. Such vehicles are vulnerable to rollover and stability issues when negotiating curves at a normal operating speed. Therefore, the tilting capability is crucial to such vehicles. Existing solutions, which mechanically connect the wheel module on both sides and synchronize their movement, still have room for further improvement. The extra links for synchronization not only take up space on compact urban vehicles, but also introduce additional mass to the light-weighted body. The novel tilting mechanism introduced in this work utilizes hydraulics to replace mechanical connections to generate the tilting motion. An interconnected hydro-pneumatic suspension system is adopted to provide the desired bump and roll stiffness for narrow urban vehicle applications. Two independently controlled hydraulic pumps are connected to the hydraulic suspensions to provide the tilting, as well as riding height change capabilities. The integration of the tilting system with suspension reduces the system weight and packing size, both of which are vital to the success of narrow urban vehicles. All the functionalities are illustrated, modelled and examined in the simulation studies, which prove the feasibility of the proposed system on narrow urban vehicle applications resulting in more functionalities with lower complexity and weight.